Studies on the biological activity of Fluazifop-butyl - Chandrasena, J.P.N.R. (Faculty of Science, University of Colombo, 1983)
Several aspects of the biological activity of fluazifop-butyl, a new selective, post-emergence herbicide for grass-weed control, were investigated with particular reference to its action against couch-grass (Agropyron repens). The herbicide readily kills A.repens, achieving a high degree of rhizome-bud kill at the same time. A dose of 1.0 kg ha-l was sufficient to achieve 100% bud kill under glasshouse conditions in plants up to 16-weeks old, if uptake and translocation occurred undisturbed for 48 h. ...